Coupled effects of Mn(ii), pH and anionic ligands on the reactivity of nanostructured birnessite. Issue 12 (8th December 2020) - Li, Qinzhi; Pokharel, Rasesh; Zhou, Lian; Pasturel, Mathieu; Hanna, Khalil
Abstract : Dissolved Mn(ii ), pH and naturally occurring anions exhibit combined suppressive effects on the reactivity of nanostructured birnessite. Abstract : While the oxidative capacity of nanostructured birnessite-type manganese oxide has been widely investigated, no comprehensive work exists on the combined effects of dissolved Mn(ii ), pH and inorganic anions on sorption and redox reactions of organic contaminants with MnO2 . Herein, we have showed how molecular interactions of two contrasting organic contaminants, pipemidic acid (PIP) and bisphenol A (BPA), with MnO2 surfaces controlled the removal kinetic behavior, which depended on contaminant type and coexisting anions. Competition between the contaminant and Mn(ii ) for binding at the edge sites determined the initial kinetic step, while buildup of Mn(ii ) at both edge and vacancy sites continuously decreased adsorption and subsequent oxidation over time. Redox interactions of Mn(ii ) with MnO2 surfaces was a pH-dependent process, and high pH favored Mn(ii ) removal and the comproportionation reaction, thus decreasing the adsorption and oxidation processes. At low Mn(ii )/MnO2 ratio, MnO2 adsorbed more effectively anions such as phosphate or silicate, thus reducing interactions with organic compounds. These results highlight the combined suppressive effects of Mn(ii ), pH and naturally occurring anions on the reactivity of nanostructured birnessite and have strong implications on the fate of organic contaminants in terrestrial and aquatic environments.